Kongedatteren og hendes ghost writer: Nyt syn på tilblivelsen af Leonora Christinas franske selvbiografi (1673) - Olden-Jørgensen, Sebastian (Danske Studier, 2023)
On the first of May 1673 Leonora Christina (1621-98), daughter of King Christian IV and his morganatic second wife Kirsten Munk, finished her so called French autobiography (preserved in her own hand in The Royal Library in Copenhagen and issued in a new critical edition in 2021). The text is addressed to some »Monsieur« and gives a charming and rather smug account of her turbulent life as viewed from the prison cell in Copenhagen where she had been locked up since 1663. Traditionally the anonymous addressee has been identified as the scholar Otto Sperling the younger (1634-1715) who is supposed to have used the autobiography as the main source for a short Latin biography of her in his De foeminis eruditis, an unfinished collection of 1.399 learned women of all nations and ages preserved in the manuscript collection of The Royal Library in Copenhagen. A systematic comparison between Sperling’s Latin biography of Leonora Christina (soon to be published in Fund og Forskning i Det Kongelige Biblioteks Samlinger) and the French autobiography demonstrates conclusively that Sperling’s text is not based on hers, and it is therefore highly improbable that he is the »Monsieur« for whom she wrote her life’s story. The real addressee possibly is Admiral Henrik Bjelke (1615-83) who fits the bits of information on »Monsieur« that can be gathered from the French autobiography and other sources. This new understanding of the text’s genesis not only changes the identity of the original addressee and offers a better explanation of several details such as the autobiography’s unmitigated aristocratic bias. It also means that Sperling’s Latin biography is not merely an adaption of another known text but an original source based on a series of interviews with Leonora Christina around 1690. This brings his text in much greater proximity to the old lady herself.